2014
DOI: 10.1165/rcmb.2013-0092oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transglutaminase 2, a Novel Target for Pulmonary Fibrosis, by Two Small Electrophilic Molecules

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by progressive fibrotic destruction of normal lung architecture. Due to a lack of effective treatment options, new treatment approaches are needed. We previously identified transglutaminase (TG)2, a multifunctional protein expressed by human lung fibroblasts (HLFs), as a positive driver of fibrosis. TG2 catalyzes crosslinking of extracellular matrix proteins, enhances cell binding to fibronectin and integrin, and promotes fibronectin expression. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 53 publications
4
41
0
Order By: Relevance
“…However, studies on other airway diseases, such as cystic fibrosis, idiopathic pulmonary fibrosis, and lung cancer, support a central role for Tgm2 in aberrant pulmonary wound healing and have led to the development of Tgm2 inhibitors for the treatment of these diseases. 54,[56][57][58][59] Thus airway Tgm2 levels should be assessed in asthmatic patients and patients with chronic rhinosinusitis with nasal polyps (CRSwNP) and correlated to disease severity to investigate whether Tgm2 might represent a therapeutic target in asthma or nasal polyposis. Because Tgm2 expression can be modulated by DNA methylation 60 or oxidative stress, 61 which are both strongly influenced by age, 62,63 future studies should clarify the role of these factors in age differences in levels of Tgm2 and its regulatory targets in the setting of airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on other airway diseases, such as cystic fibrosis, idiopathic pulmonary fibrosis, and lung cancer, support a central role for Tgm2 in aberrant pulmonary wound healing and have led to the development of Tgm2 inhibitors for the treatment of these diseases. 54,[56][57][58][59] Thus airway Tgm2 levels should be assessed in asthmatic patients and patients with chronic rhinosinusitis with nasal polyps (CRSwNP) and correlated to disease severity to investigate whether Tgm2 might represent a therapeutic target in asthma or nasal polyposis. Because Tgm2 expression can be modulated by DNA methylation 60 or oxidative stress, 61 which are both strongly influenced by age, 62,63 future studies should clarify the role of these factors in age differences in levels of Tgm2 and its regulatory targets in the setting of airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, less conventional methods that abolish TG2 activity by limiting its expression are also being pursued. Upstream inhibitors of the extracellular signal-regulated kinase (ERK) pathway that down-regulate TG2 expression and small interfering RNA (siRNA) have successfully demonstrated preclinical potential as antifibrotic therapies (63,64). TG2 siRNA coupled with liposome delivery yielded effective organ-specific targeting to the liver and lungs in mice (64).…”
Section: Tissue Transglutaminasementioning
confidence: 99%
“…[18] Regarding the therapeutic potential of TG2, a recent study demonstrated that two small electrophilic compounds inhibit TG2 and its pro-fibrotic activities in human lung fibroblasts. [20] The in vivo therapeutic potential of these compounds in fibrotic lung disease is of great interest, also in relation to fibulin-5 expression.…”
Section: Expert Opinion: Fibulin-5 As a Therapeutic Targetmentioning
confidence: 99%